Población, azúcar e industria rural en Tucumán, Argentina - Bolsi, Alfredo (Geographicalia, 2016)
In the origins and development of the sugar landascape of Tucumán, responsible for the 35% of the GDP of this province- two stages have been detected: a pre industrial one which took place between the end of the 18th century and the last third of the 19th, and an industrial process from then on to the present. In this work the interest has been centered in the origins of that pre industrial stage. It is believed that the rapid population increase in the context of an agrarian landscape with active rural participation , with an important land division and -among other factors- a strong handmade (craftmanship) development and a dominant presence of the market and of the merchants, it has built the main pattern wich could explain the origins of this agrarian region and landscape of sugar.